2020
DOI: 10.1101/2020.04.09.035055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Molecular Landscape of Asian Breast Cancers Reveals Clinically Relevant Population-Specific Differences

Abstract: 2Molecular profiles of breast cancer have contributed to an improved understanding of the 3 disease, enabled development of molecular prognostic signatures to guide treatment decisions 4 and unveiled new or more accurate therapeutic options for breast cancer patients. However, 5 the extent to which differences in genetic, environmental and lifestyle factors influence 6 molecular profiles in different populations remains poorly characterised, as relatively few 7 large-scale molecular studies of breast tumours i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 78 publications
(104 reference statements)
0
23
0
Order By: Relevance
“…We found that there were no significant differences in the frequencies of molecular subtypes between A3B germline deletion carriers and noncarriers (Figure 3A), suggesting that germline A3B deletion does not significantly affect molecular subtype. We then examined the mutational profiles of these tumours by examining the nonsynonymous mutations in the 10 most frequently affected genes in the MyBrCa cohort 24 , comparing patients with different germline A3B copy number, but also did not find any significant differences (Figure 3B). We found that germline A3B deletion was marginally associated with a higher number of C‐to‐T or G‐to‐A transitions in PIK3CA (Supplementary Figure 8A), but not in the other nine genes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that there were no significant differences in the frequencies of molecular subtypes between A3B germline deletion carriers and noncarriers (Figure 3A), suggesting that germline A3B deletion does not significantly affect molecular subtype. We then examined the mutational profiles of these tumours by examining the nonsynonymous mutations in the 10 most frequently affected genes in the MyBrCa cohort 24 , comparing patients with different germline A3B copy number, but also did not find any significant differences (Figure 3B). We found that germline A3B deletion was marginally associated with a higher number of C‐to‐T or G‐to‐A transitions in PIK3CA (Supplementary Figure 8A), but not in the other nine genes.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that the deletion only indirectly affects the immune microenvironment via APOBEC hypermutation, which is itself only weakly associated with expression of the A3A-B hybrid isoform, leading to a very weak overall association between germline A3B copy number and the immune microenvironment. Another possibility is that the immune profiles of breast cancers in Asian women already have enriched immune profiles compared to cancers in women of European descent, 24,40 thereby reducing the impact of germline A3B polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations